Advancing precision medicine in esophageal squamous cell carcinoma using patient-derived organoids - Suya Shen; Bing Liu; Wenyan Guan; Ziyao Liu; Yuqing Han; Yingzhe Hu; Yiqiang Chen; Siyuan Liu; Jian He; Zhiwen Li; Weifeng Tang; Pengju Zhang; et al. (Journal of Translational Medicine)
Abstract Background Patient-derived organoids (PDOs) represent a promising approach for replicating the characteristics of original tumors and facilitating drug testing for personalized treatments across diverse cancer types. However, clinical evidence regarding their application to esophageal cancer remains limited. This study aims to evaluate the efficacy of implementing PDOs in clinical practice to benefit patients with esophageal squamous cell carcinoma (ESCC). Methods Fresh surgical biopsies were obtained from patients with esophageal cancer for the establishment of PDOs. These PDOs were subsequently characterized through histological analysis. A customized drug panel, based on standard-of-care chemotherapy regimens, was applied to the PDOs. The resulting drug sensitivity profiles were then correlated with the clinical responses observed in individual patients undergoing actual treatment. Results A total of 34 PDOs were successfully established with a 61.8% success rate. The classification method based on chemotherapy sensitivity closely corresponded to clinical responses. The paclitaxel plus cisplatin (TP)-sensitive group demonstrated significantly longer progression-free survival (PFS) compared to the resistant groups, Hazard ratio (HR), 5.12; 95% confidence intervals (CI 0.58–44.71; p < 0.05), thus illustrating the potential of this approach for guiding personalized treatment strategies. Conclusion Organoid biobanks were established across multiple institutes to facilitate PDOs-based functional precision medicine. The findings demonstrate that this framework offers robust predictive value in clinical settings, enhances precision therapeutics, and advances drug discovery for esophageal cancer. Graphical Abstract